Impact of Nodal Level Distribution on Survival in Oral Cavity Squamous Cell Carcinoma: A Population‐Based Study. (15th March 2016) - Marchiano, Emily; Patel, Tapan D.; Eloy, Jean Anderson; Baredes, Soly; Park, Richard Chan Woo
Abstract : Objective: Regional lymph node metastasis is an important prognostic factor in squamous cell carcinoma of the head and neck, decreasing survival by up to 50%. Oral cavity squamous cell carcinoma (OC‐SCCa) most commonly spreads to levels I, II, and III. Study Design: Retrospective analysis of a population‐based tumor registry. Setting: Academic medical center. Subjects and Methods: The Surveillance, Epidemiology, and End Results (SEER) database was queried for cases of OC‐SCCa from 2004 to 2011 (22, 973 cases). Resulting data including patient demographics, clinicopathological features, topographical distribution of nodal metastasis, and survival based on lymph node level involvement were analyzed. Results: In total, 8281 patients were identified with OC‐SCCa who underwent neck dissection. Level I, closely followed by levels II and III, represented the most commonly involved nodal basins. The 5‐year disease‐specific survival (DSS) for patients with only level I, II, or III was 42.0% compared with 30.6% for the level IV group ( P <. 0001) and 26.4% for the level V group ( P <. 0001). Surgery with adjuvant radiotherapy improved 5‐year DSS for patients with level I to III, level IV, and level V neck disease compared with surgery alone (50.7% vs 48.6%, P =. 0109; 39.9% vs 23.2%, P <. 0001; and 33.3% vs 9.1%, P =. 0005, for levels I‐III, IV, and V, respectively). Conclusion: Oral cavity squamous cell carcinoma most commonly involves nodal levels I, II, and III. Involvement of nodal level IV or V portends a worse prognosis than patients with only level I to III disease, and multimodality therapy should be considered for these patients.